HUBUNGAN LINGKUNGAN KERJA DENGAN KINERJA PETUGAS PADA PENYERAHAN DOKUMEN REKAM MEDIS INSTALASI RAWAT INAP I RSUD DR. SAIFUL ANWAR MALANG - Fadilah Akbar Filayati (Jurnal Ilmu Kesehatan Masyarakat, 2017)
The return time of medical record documents is one of the performance indicators medical record document submission officer, according to the Medical Record Manual Book, standard of the time to return of medical record document in inpatient is 2 x 24 hours after the patients out of the hospital. Result of preliminary studies found there were medical record documents late, average of medical record documents late were 45,28 % at Inpatient Instalation I. This research designed to analyze the relation of work environment with performance of medical record document submission officer. The type of this research was analytical with cross sectional approach. The result of this research was work culture of officer was very good (64%). Leadership effect to officer was effective enough (56%). Relationship between employee and boss was very good (68%), and Compensation of officer was very good (88%). The result of analysis showed that there was a correlation between work culture with officer performance (p=0,019), there was correlation between leadership with officer performance (p=0,018), there was no correlation between aspect of relationship of employee and boss with officer performance (p=0,688), and there was no correlation between compensation with officer performance (p=0,263). The conclusion of this research is the work culture and leadership is work environment that correlation with officer performance in Instalation of inpatient I RSUD Dr. Saiful Anwar Malang Keywords: Work environment, performance, medical record document